Increasing Public Awareness To Avoid Business Transactions That Contain Elements Of Riba In Kubang Jaya Village - Winario, Mohd; Zakir, Muhammad; Khairi, Rifqil; Sudirman, Wahyu Febri Ramadhan; Fithriyana, Rinda; Maini, Nur; Irmawanti, Irmawanti (Journal of Community Sustainability, 2024)
This community service was carried out in Kubang Jaya Village, Siak Hulu District, Kampar Regency. The aim of this community service is to increase public awareness of avoiding business transactions that contain elements of usury and to find out the level of success of the community service program for business transactions that contain elements of usury. The methods used in this community service activity are counseling, presentations and discussions. The results of the service show that: First, the people of Kubang Jaya Village, Siak Hulu District, Kampar Regency's understanding of business transactions varies, some already understand, some are still doubtful, some even don't understand, Second, the objectives of the service activity program have been achieved. community for the Kubang Jaya Village Community, Siak Hulu District, Kampar Regency, all programs that have been carried out in collaboration between business owners and servants have been carried out in accordance with the event schedule and predetermined time.